Added-value interfaces to asteroid photometric and spectroscopic data in the Gaia database. Issue 2 (15th July 2018) - Torppa, Johanna; Granvik, Mikael; Penttilä, Antti; Reitmaa, Jukka; Tudose, Violeta; Pelttari, Leena; Muinonen, Karri; Bakker, Jorgo; Navarro, Vicente; O'Mullane, William
Abstract: We present two added-value interfaces (AVIs) for analyzing photometric and spectroscopic data observed by the Gaia satellite. The Gaia Added-Value Interface for Temporal Analysis (GAVITEA) is used to calculate an estimate for the spin state and shape of an asteroid from its photometric data, and the Gaia Added-Value Interface for Spectral Classification (GAVISC) provides tools to define the taxonomic type and surface absorption coefficient based on spectroscopic asteroid data. Computations are mainly carried out using well-known methods of asteroid data analysis but the AVIs also offer the possibility to test novel methods that are specifically developed for analyzing temporally sparse photometric data, typical for Gaia.